Factors affecting adaptive performance among working mothers during Covid-19 crisis - Mohd. Nazrul, Mohd. Nasir (2021)
Coronavirus 2019 (COVID-19) had highly impact performance of all organizational as well as individual career performances. Working mothers are the group of people who are facing their daily difficulty in managing work needs and family needs. To understand adaptive performance behavior towards their segmentation approach, understanding of the view of the factors such as individual improvisation, individual flexibility, intellectual capital, self-efficacy and work-life balance were considered to be examined in the study. Thus, this study is conducted for working mothers in Malaysia because they are one of the most affected in current pandemic Covid-19 impact that facing disturbances in their career against daily mother’s routines. This research was used a survey methodology by questionnaire, then analysed by using descriptive analysis, correlation and regression analysis. 245 working mothers were obtained as a sample of this study. The findings were evidently proved that individual improvisation, intellectual capital and self-efficacy were positively associated and abled to influence working mothers’ adaptive performance during pandemic of COVID-19. However, it has found that individual flexibility and work-life balance have no significant influence towards working mothers’ adaptive performance during pandemic COVID-19. Nevertheless, all the findings in this study could contribute to both theorists and managerial practitioners.